Neosaxitoxin, a Long-Lasting Local Anesthetic and its Potential Clinical Applications in Horses - Dörner, Cristóbal; Del Campo, Miguel; Lagos, Nestor (Austral Journal of Veterinary Sciences, 2023)
Neosaxitoxin (NeoSTX) is a toxin that binds to the voltage-gated sodium channels therefore, inhibiting the neuronal impulse. The present study was conducted to explore the properties of NeoSTX and to evaluate its effects when injected as a perineural nerve block in horses. A group of five client-owned mature Warmblood horses exhibiting clinical signs of unilateral foot pain were enrolled in the study. For inclusion, lameness should subside after a palmar digital nerve block (PDNB) using 2 mL of 2% lidocaine administered over the medial and lateral palmar digital nerves of the affected limb (Day 0). Lameness was assessed using the AAEP lameness grading scale and skin sensitivity was judged objectively using a pressure algometer. On day 1, 5µg of NeoSTX was injected, then on day 4, 10 µg of NeoSTX was administered. Lameness examination and skin sensitivity were evaluated at 3, 5,10, 15,30, 60, 90 minutes, and every hour until the effects of the nerve block were no longer detectable. When effects of NeoSTX was compared to effects of lidocaine at 2% there were no statistical differences in the onset of the anesthetic effect, measured as the time of start of desensitization of the skin and the time of complete desensitization or lameness resolution, nonetheless there was a significant difference in the return of skin sensation or lameness, showing a clear long-lasting nociceptive blocker effect of NeoSTX. In conclusion, results of this study suggest NeoSTX can potentially be used as an alternative to conventional local anesthetics drugs when a long-lasting effect is desired, for example as a part of a multimodal approach for pain management, as a local anesthetic for surgical procedures or to control chronic pain in some musculoskeletal disorders. However, more studies are needed to evaluate its use as long-lasting anesthetic effects in the aforementioned situations.